A multivariate probit analysis on the factors influencing the adoption of water saving technologies by rice farmers in Sto. Domingo, Nueva Ecija - Raguindin, Daniel R.; De Vera, Eiffel A (2012)
We study the adoption of rice farmers of some water saving technologies (WST) such as controlled irrigation, direct seeding, land leveling and aerobic rice system. A multivariate probit model for the adoption of each WST is constructed since usage of different technologies exhibit correlation. The significant factors that influence the WST adoption are education, experience in rice farming, family income of the farmers, and size of manpower involved in farming. Higher education is needed to enhance the ability to successfully implement the WST. Experience in rice farming, i.e., the number of years a farmer is involved in rice management and production, increases the likelihood of adoption among farmers. Farmers with high income have lower likelihood of adoption since the production system in place is already efficient. Furthermore, a farmer is more likely to adopt the technology as more manpower is involved in the production system. The estimated model indicated that the probability of adoption of controlled irrigation is higher than the other three WST. In addition, the adopters of WST had greater output in terms of the harvested rice.
Keywords: Rural water supply -- Nueva Ecija; Probits